2014
DOI: 10.1111/cen.12381
|View full text |Cite
|
Sign up to set email alerts
|

Plasma omentin and adiponectin levels as markers of adipose tissue dysfunction in normal weight and obese women with polycystic ovary syndrome

Abstract: Our results suggest secondary to insulin resistance and hyperandrogenism impairment of hormonal stroma adipose tissue function in PCOS, independent of nutritional status. Contrarily, the adipocyte hormonal dysfunction is primarily dependent on excessive fat accumulation. It seems that the AOR may be useful in the assessment of adipose tissue dysfunction not only in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
(79 reference statements)
6
39
0
1
Order By: Relevance
“…Additionally, our study revealed an inverse correlation between circulating AMH and omentin‐1 levels that was strengthened by the results of multiple regression analysis showing that circulating AMH level variability is explained by omentin‐1 levels, independent of parameters describing nutritional status. The inconsistency seems to be the result of differences in adipose tissue hormonal function in PCOS and in non‐PCOS women, as was described in our previously published studies . We observed lower apelin‐36 and adiponectin levels but higher leptin and omentin‐1 levels in obese compared to normal weight PCOS women .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, our study revealed an inverse correlation between circulating AMH and omentin‐1 levels that was strengthened by the results of multiple regression analysis showing that circulating AMH level variability is explained by omentin‐1 levels, independent of parameters describing nutritional status. The inconsistency seems to be the result of differences in adipose tissue hormonal function in PCOS and in non‐PCOS women, as was described in our previously published studies . We observed lower apelin‐36 and adiponectin levels but higher leptin and omentin‐1 levels in obese compared to normal weight PCOS women .…”
Section: Discussionsupporting
confidence: 73%
“…So far, there is a lack of studies that assess the relationships between circulating AMH and adipokines levels in PCOS. Our previously published studies revealed changes of circulating adiponectin, apelin, leptin and omentin‐1 levels in PCOS …”
Section: Introductionmentioning
confidence: 91%
“…Excessive visceral fat depot and its hormonal disturbances seem to play a role in hormonal and metabolic disturbances in PCOS (28,29,30,31,32). As described earlier, the novel adipokine FGF21 may play a role in the PCOS-related metabolic disturbances.…”
Section: Introductionmentioning
confidence: 72%
“…Notably, the inverse relation between omentin levels on the one hand and 2-h glucose, 2-h insulin and ISI (composite), which represents an OGTT-derived measure of insulin sensitivity that is more closely related to clamp-measured insulin sensitivity than HOMA-IR (23), on the other hand remained significant after adjustment for BMI, but not after adjustment for lipids or adiponectin. Some (10,26), but not other (7,11,27,28), studies reported inverse associations between omentin and fasting glucose in univariate analyses. One study reported inverse associations with fasting glucose, 2-h glucose and HbA1c in univariate, but not in multivariate analyses (12).…”
Section: Omentin and Glucose Metabolismmentioning
confidence: 93%
“…One study reported inverse associations with fasting glucose, 2-h glucose and HbA1c in univariate, but not in multivariate analyses (12). Results were also conflicting for fasting insulin and HOMA-IR with several studies observing inverse associations for insulin (27) and HOMA-IR (8,10,11,12,14,27), whereas others reported no significant relationships for insulin (7,11,12) or HOMA-IR (7, 26). Overall, the comparison of study results is hampered by the differences in sample selection, sample size and statistical …”
Section: Omentin and Glucose Metabolismmentioning
confidence: 99%